Consent. Issue 5 (May 2018) - Love, Christopher; Pace, Nick
Abstract: Morally, 'consent' allows an autonomous patient to determine what treatments they will accept or refuse. The law relating to medical consent protects such self-determination, and allows for treatment decisions to be made for patients who cannot decide for themselves. Consent is valid if it is given voluntarily by a competent patient and is based on the information provided to them. Information is provided about what is to be done and why, and what the foreseeable risks and consequences of treatment are. The onus is on the clinician to explain material risks that are significant to the patient. Competent patients understand, remember and use the information provided to them to either consent to, or refuse, treatment. Patients lacking capacity are protected by The Mental Capacity Act 2005, which obliges that medical treatment decisions made by third parties (doctors, defined proxies or the courts) to be both necessary and in the patient's best interests, in the absence of a valid advance directive. Consent relating to children, pregnant women, the mentally ill, emergencies and teaching requires special consideration.